A Comparation Between Frame-Based and Robot-Assisted in Stereotactic Biopsy - Hu, Yue; Cai, Pu; Zhang, Huawei; Adilijiang, Aihemaitiniyazi; Peng, Jun; Li, Yun; Che, Shanli; Lan, Fei; Liu, Changqing (Frontiers in Neurology, 2022)
Introduction: Frame-based stereotactic biopsy is well-established to play an essential role in neurosurgery. In recent years, different robotic devices have been introduced in neurosurgery centers. This study aimed to compare the SINO surgical robot-assisted frameless brain biopsy with standard frame-based stereotactic biopsy in terms of efficacy, accuracy and complications. Methods: A retrospective analysis was performed on 126 consecutive patients who underwent stereotactic biopsy at Chongqing Sanbo Jiangling Hospital between August 2018 and December 2021. All patients were divided into the frame-based group (n=22) and the SINO surgical robot-assisted group (n=104). The data collected included clinical characteristics, diagnostic yield, operation times, accuracy, and postoperative complications. Results: There was no significant difference in diagnostic yield between the frame-based group and the SINO surgical robot-assisted group (95.45% vs. 98.08%, p>0.05). The mean operation time in the SINO surgical robot-assisted group was significantly shorter than in the frame-based group (29.36±13.64 min vs. 66.23±57.23 min). The entry point error in the frame-based group was significantly higher than in the robot-assisted group (1.36±0.47 mm (0.47-2.30) vs. 0.92±0.27 mm (0.35-1.65), P＜0.001). Finally, there was no significant difference in postoperative complications between the two groups. Conclusion: The SINO surgical robot-assisted platform is efficient and provides a reasonable alternative to stereotactic biopsy in neurosurgery, reducing operation time and improving accuracy without increasing postoperative complications.